COMPARISON ANALYSIS OF OPTIMAL PORTFOLIO PERFORMANCE ESTABLISHED FROM LQ45 INDEX STOCK WITH MANDIRI MUTUAL MUTUAL FUNDS PORTFOLIO INVESTA EQUITY ASEAN 5 PLUS - Ahmad Fuady Hasibuan; Isfenti Sadalia; Khaira Amalia Fachrudin (International Journal of Educational Review, Law And Social Sciences (IJERLAS), 2023)
The increase in the number of investors becomes a huge potential to increase the capacity of the capital market. Among the instruments of investment in the stock market, shares are the most frequently traded. The participation of local investors in investing in the capital market cannot be separated from the expectations of profit or return that can be obtained as well as the risks attached to investment instruments. Risks in stock investments can be minimized by reducing them to a minimal point through the process of diversifying stocks by forming a portfolio. This type of research is descriptive research with a quantitative approach. The stock candidate population used in the formation of the Optimal Portfolio is all of the shares classified into the LQ45 Index. While the sample of stock candidates included in the portfolio formation is 41 stocks with purposive sampling technique. The type of data used is secondary data with data collection techniques documentation. In forming the portfolio used the single index model and constant correlation model. While to measure the performance portfolio used measurement scales Sharpe Index, Treynor Index and Jensen Alpha. Based on the performance measures of the Sharpe Index, Treynor Index and Jensen Alpha, the portfolio formed from LQ45 shares using a single index model has lower performance than the portfolio performance formed from LQ45 stock by using a constant correlation model. Based on the Treynor Index performance measure, the portfolio formed from LQ45 stock using a single index model has higher performance than the Mandiri Investa Equity Asean 5 Plus portfolio.